A single-centre observational cohort study of admission National Early Warning Score (NEWS). (July 2015) - Abbott, Tom E.F.; Vaid, Nidhi; Ip, Dorothy; Cron, Nicholas; Wells, Matt; Torrance, Hew D.T.; Emmanuel, Julian
Abstract: Introduction: Early warning scores are commonly used in hospitals to identify patients at risk of deterioration. The National Early Warning Score (NEWS) has recently been introduced to UK practice. However, it is not yet widely implemented. We aimed to compare NEWS to the early warning score currently used in our hospital – the Patient at Risk Score (PARS). Methods: We conducted a prospective observational cohort study of all adult general medical patients admitted to a single hospital over a 20-day period. Physiological data and early warning scores recorded in bedside charts were collected on admission and a NEWS score was retrospectively calculated. The patient notes were reviewed at 48 h after admission. The primary outcome was a composite of critical care admission or death within 2 days of admission. The secondary outcome was hospital length of stay. Results: NEWS was more strongly associated with the primary outcome than PARS (odds ratio 1.54, p  < 0.001 compared to 1.42, p  = 0.056). A NEWS of 3 or more was associated with the primary outcome (odds ratio 7.03, p  = 0.003). Neither score was correlated with hospital length of stay. Conclusion: NEWS on admission is superior to PARS for identifying patients at risk of death or critical care admission within the first 2 days of hospital stay. Current guidelines advocate a threshold of 5 for triggering a clinical review. However, since a score of 3 or more was associated with a poor outcome, this recommendation should be reviewed. Both scores were poor predictors of hospital length of stay.